The influence of operation time for hip hemiarthroplasty on complication rates and mortality in patients with femoral neck fracture: a retrospective data analysis - Nikolai Ramadanov; Mikhail Salzmann; Maximilian Voss; Robert Hable; Hassan Tarek Hakam; Robert Prill; Dobromir Dimitrov; Roland Becker (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background The aim of the present study was to investigate the influence of various factors, in particular operation time, on mortality and complication rates in patients with femoral neck fractures who have undergone hip hemiarthroplasty (HHA) and to determine a cut-off value above which mortality and complication rates increase significantly. Methods Cases of patients with femoral neck fracture treated with HHA between 1 January 2017 and 31 December 2023 were screened for eligibility. Multiple logistic regressions were calculated to determine which factors (patient age, experience of surgeon, patient sex, ASA score, time to surgery, operation time) influenced the incidence of complications and mortality. The exact cut-off value for complications and mortality was determined using the Youden index of the ROC curve (sensitivity vs. specificity) of logistic regression. Results A total of 552 patients were considered eligible for this study. During the 90-day follow-up period after HHA, 50 deaths and 34 complications were recorded, giving a mortality rate of 9.1%, and a complication rate of 6.2%. Of the 34 complications recorded, 32.3% were infections, 14.7% dislocations, 20.7% trochanteric avulsions, 11.8% periprosthetic fractures, 11.8% nerve injuries, and 8.8% deep vein thrombosis. The odds ratio (OR) of a patient experiencing a complication is 2.2% higher for every minute increase in operation time (Exponential Beta − 1 = 0.022; p = 0.0363). The OR of a patient dying is 8.8% higher for each year increase in age (Exponential Beta − 1 = 0.088; p = 0.0007). When surgery was performed by a certified orthopaedic surgeon the mortality rate lowered by 61.5% in comparison to the surgery performed by a trainee (1 – Exponential Beta = 0.594; p = 0.0120). Male patients have a 168.7% higher OR for mortality than female patients (Exponential Beta − 1 = 1.687; p = 0.0017). Patients with an operation time of ≥ 86 min. have a 111.8% higher OR for mortality than patients with an operation time of < 86 min. (Exponential Beta – 1 = 1.118). Conclusion This retrospective data analysis found that the risk of a patient experiencing a complication was 2.2% higher for every minute increase in operation time. Patients with an operation time above the cut-off of 86 min had a 111.8% higher risk of mortality than those with an operation time below the cut-off. Other influencing factors that operators should be aware of include patient age, male sex, and operator experience.